Uji Aktivitas Hepatoprotektor pada Tikus Model Kanker Payudara yang Diinduksi Benzo(A)Piren Setelah Pemberian Ekstrak Metanol Daun Biwa (Eriobotrya japonica Lindl) - Fitri Elizabrth Hasibuan; Widya Syahfitri; Salomo Hutahaean; Syafruddin Ilyas; Febry Rahmadani Hasibuan (JURNAL BIOS LOGOS, 2025)
This study aimed to evaluate the hepatoprotective activity of methanolic extract of loquat (Eriobotrya japonica Lindl) leaves in breast cancer model rats induced by benzo(α)pyrene. This study used a completely randomized design with five groups: Group I as the negative control, Group II as the positive control (administered BaP 50mg/KgBW), and three treatment groups receiving methanolic extract of loquat leaves at doses of 200 mg/kg BW, 300 mg/kg BW, and 400 mg/kg BW for 30 days. Blood serum samples from the breast cancer model rats were analyzed to determine SGPT and SGOT levels using the IFCC method. Data were statistically analyzed using Analysis of Variance (ANOVA) followed by Tukey’s HSD post-hoc test. The results showed no significant differences between the treatment and control groups for SGOT (F(4,20) = 0.7123, P = 0.593) and SGPT (F(4,20) = 0.4460, P = 0.774) levels. Based on these findings, it can be concluded that administration of methanolic extract of loquat leaves did not cause liver function impairment in the breast cancer model rats. These results support the potential of loquat leaf extract as a hepatoprotective agent, particularly in maintaining stable SGPT and SGOT levels in breast cancer conditions.